Effects of CEO Identity on Non-family Managers’ Pay Dispersion in Family Firms: A Social Comparison Perspective - Zhang, Wei; Chen, Ling; Zhu, Jian-an (Frontiers in Psychology, 2021)
The fairness of compensation has been a prominent focus for non-family managers, and pay dispersion, which reflects compensation fairness, has attracted much attention from scholars. Based on social comparison theory, this study investigates the factors that affect the pay dispersion between CEO and non-family managers. In family firms, the role of CEO, which is central in corporate governance, can be filled by either a family or a non-family member. This study provides insights into how the identity of the CEO affects pay dispersion and investigates the moderating effects of CEO tenure and institutional environment. Using the data of Chinese listed family firms from 2009 to 2015, the results show that the presence of non-family CEOs could decrease the pay dispersion between CEO and non-family managers. Empirical evidence also supports that the negative relationship between CEO identity and pay dispersion weakens when CEO tenure increases and the institutional environment matures.